"A strange thrill": Isabella Bird and the fugitive community of travellers. Issue 1 (2nd January 2017) - Kumojima, Tomoe
ABSTRACT: What distinguishes Isabella Bird from her contemporary female travellers to Japan is her ambitious inland journey beyond the established contact zone. This culminates in an ethnographic achievement underpinned by close interaction with the local people and their culture. This essay examines previously neglected textual manifestations of cross-cultural affinity between Bird and Japanese and Ainu people in Bird's Unbeaten Tracks in Japan (1880). The travelogue presents rare instances of a fleeting sense of community which emerges across multiple differences of nationality, race, culture and language. As a country that is outside the British sphere of influence in a strict sense, Japan presents a unique space where colonial barriers disintegrate. The essay finally connects the moments of solidarity created in Bird's work to Jean-Luc Nancy's idea of "non-identitarian alliance", and suggests ways in which the study of travel writing might contribute to philosophical and ethical debates.